Mainstreaming gender into global health programming to improve women's health. Issue 4 (2nd April 2020) - Gupta, Jaya; Betron, Myra; Brown, Jane; Morgan, Rosemary
Abstract: In this paper, a case is made for mainstreaming gender into global women's health programming and policies. The potential implications of conflating "gender" with "women'" in the design and evaluation of women's health programming are first considered. HIV/AIDS case studies are then used to depict examples of (a) where gender has been well integrated and (b) where policies fall short of gender mainstreaming. Finally, practical approaches to mainstream gender in a meaningful way into the design and evaluation of women's health programming and policies are provided for practitioners and researchers.